2012
DOI: 10.5539/res.v4n2p124
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Locus of Control Expectancy on Level of Well-Being

Abstract: This paper investigates the impact of locus of control, a psychological social learning theory that is rigorously researched for its implications on leadership qualities, on the level of happiness of an individual. The primary research strategy employed was the survey strategy. Participants were asked to fill in a questionnaire that was designed to test, amongst other variables, their locus of control and level of happiness. The Spearman Rank Correlation hypothesis test was used to test the data for significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 59 publications
5
62
2
5
Order By: Relevance
“…Studies on subjective well-being emphasize that locus of control is essentially important to explain well-being besides the ''big five'' (e.g., April, Dharani, & Peters, 2012;DeNeve & Cooper, 1998;Diener et al, 1999;Stocks, April, & Lynton, 2012), with internal locus of control correlating positively with subjective well-being and external locus of control negatively. Moreover, BJW research has shown that internal locus of control is positively associated with BJW (Lipkus, 1991;Rim, 1981;Rubin & Peplau, 1973, 1975Witt, 1989;Zuckerman & Gerbasi, 1977; for a review, see also Furnham & Procter, 1989).…”
Section: Control Factorsmentioning
confidence: 98%
“…Studies on subjective well-being emphasize that locus of control is essentially important to explain well-being besides the ''big five'' (e.g., April, Dharani, & Peters, 2012;DeNeve & Cooper, 1998;Diener et al, 1999;Stocks, April, & Lynton, 2012), with internal locus of control correlating positively with subjective well-being and external locus of control negatively. Moreover, BJW research has shown that internal locus of control is positively associated with BJW (Lipkus, 1991;Rim, 1981;Rubin & Peplau, 1973, 1975Witt, 1989;Zuckerman & Gerbasi, 1977; for a review, see also Furnham & Procter, 1989).…”
Section: Control Factorsmentioning
confidence: 98%
“…This tendency characterises a person's perspective on selfindependence in contrast to control by others. Locus of control also determines the likelihood of a particular behaviour as well as the outcomes of engaging in such behaviour (April, Dharani, & Peters, 2012). In the context of an engineering environment, locus of control describes the capacity of engineers to shape and influence work-related outcomes such as engineering drawing, maintenance of substations and execution of technical tasks such as restoration of power in customers' houses.…”
Section: Definition Of Locus Of Controlmentioning
confidence: 99%
“…Di sisi lain, pemahaman akan locus of control juga perlu dimiliki oleh orang tua. Locus of control adalah teori pembelajaran sosial psikologis yang mengacu pada sejauh mana individu merasakan kontrol atas kehidupan mereka, dan lingkungan (April, Dharani, & Peters, 2012). Pemahaman mengenai aspek ini perlu dibutuhkan mengingat locus of control mampu meningkatkan efficacy atau kepercayaan diri serta keefektifan menahan gangguan stres (Darshani, 2014).…”
Section: Hasil Dan Diskusiunclassified